Enhancement of rural agriculture in Japan through industry-academia collaboration: a case of cloud ear mushroom production in Tottori Prefecture - Okuda, Yasuhito (Frontiers in Sustainable Food Systems, 2023)
Rural agriculture is a crucial component of social infrastructure owing to its functionalities including domestic food production, securing income sources, and cultural transmission, which are all essential for local communities. Densifying urban settlements including in Japan has resulted in population outflow from rural areas, undermining rural agriculture. Therefore, to prevent population decline in rural areas, it is effective to create innovative and attractive businesses through industry-academia collaboration. Although mushroom production can be a promising option as a model of sustainable, circular agriculture with low environmental impact, there are very few examples of collaboration. In Tottori Prefecture, Japan, among the major domestically cultivated mushrooms, attempts were made to produce cloud ear mushroom (Auricularia polytricha), which was heavily dependent on imports, through industry-academia collaboration. Along with the development of new cultivars suitable for the climate, research was conducted on optimal cultivation conditions, pest control, and post-harvest treatment. As a result, the Tottori Prefecture has achieved the highest production volume of cloud ear mushroom in Japan. This project not only supplies food but also contributes to securing an income source and social welfare because everyone can participate regardless of age or disability. In addition, because no special land or facilities are required for mushroom production, this project can be initiated at a low cost. The characteristics of this project, developed through cooperation between mushroom producers and academic institute, indicate that it is a useful model that contributes to community revitalization as well as mushroom production.